PALATAL FRACTURE FIXATION ON SEVERE PANFACIAL FRACTURE: IS THERE ANY CLINICAL SIGNIFICANCE? - Arif Tri Prasetyo; Magda Rosalina Hutagalung; Lobredia Zarasade (Jurnal Rekonstruksi dan Estetik)
Highlights: